Hubungan Dukungan Keluarga dan Pengetahuan Ibu dengan Kepatuhan Ibu Hamil dalam Mengikuti Kelas Ibu Hamil di Wilayah Kerja Puskesmas Sinaboi Kabupaten Rokan Hilir - Mansyur, Marlina; Wati, Yesi Septina; Mardiya, Rizka; Yanti, Rifa (Pusat riset dan Inovasi Nasional, 2026)
Maternal Mortality Rate (MMR) remains a major global health issue that requires serious attention. Based on the Indonesian Health Survey (Survei Kesehatan Indonesia/SKI), Indonesia’s MMR in 2022 was recorded at 195 per 100,000 live births and decreased to 189 per 100,000 live births in 2023. Although this decline indicates some progress, the figure remains far from the Sustainable Development Goals (SDGs) target of fewer than 70 maternal deaths per 100,000 live births by 2030. Therefore, various promotive and preventive efforts are needed to reduce MMR, one of which is by improving pregnant women’s compliance in attending antenatal classes. This study aimed to examine the relationship between pregnant women’s knowledge and family support and their compliance in attending antenatal classes in the working area of Sinaboi Public Health Center. This research employed a quantitative analytic method with a cross-sectional design. The total number of respondents was 136 pregnant women. The results of the univariate analysis showed that 78 respondents (57.4%) had good knowledge, 74 respondents (54.9%) received family support, and 106 respondents (78.0%) were compliant in attending antenatal classes. The Chi-square test results indicated a significant relationship between pregnant women’s knowledge and compliance in attending antenatal classes (p-value = 0.03), as well as a significant relationship between family support and pregnant women’s compliance in attending antenatal classes (p-value = 0.02). This study is expected to serve as a reference for health workers and future researchers in enhancing education and family involvement to encourage active and regular participation of pregnant women in antenatal classes.